Pengaruh Kinerja Kepala Desa Terhadap Pembangunan Ekonomi - Lilisandra Makjun; Melizubaida Mahmud; Agil Bahsoan; Usman Moonti; Sri Endang Saleh; Sudirman Sudirman; Yulianti Toralawe (State University of Gorontalo, 2023)
This research employs a quantitative approarch. Meanwhile, the data are collected through observation, interviews, and questionnaires. The research samples were 50 people in Mootawa Village, Bone Raya Subdistrict, Bone Bolango Regency. The research applies simple linier regression. The research findings indicate that the performance of the village chief positively affects economic development in Mootawa Village, Bone Raya Subdistrict, Bone Bolango Regency and it is identified from the calculation of the Pearson correlation coefficient of 0,521